PENDIDIKAN BERBASIS KEARIFAN LOKAL UNTUK MEMBENTUK KARAKTER SISWA SEKOLAH DASAR KELAS IV SDN INPRES OEBA 2 KUPANG - Magdalena Savira Balibo; Maria Renyaria Kali; Sisilia Mei Sketsi Meler Laka; Destri Fitriani Menno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of local wisdom-based education, identify the regional cultural values used in learning, and analyze their influence on the character development of fourth-grade students. The study employed a qualitative descriptive method using observation, interviews, and documentation techniques, involving homeroom teachers and fourth-grade students at SDN Inpres Oeba 2. Information was analyzed through the stages of information reduction, information presentation, and conclusion drawing. The results are expected to demonstrate that integrating local wisdom into learning can strengthen students' character, particularly discipline, responsibility, and mutual respect. These findings are also expected to serve as a reference for teachers in designing more contextual and meaningful learning that supports the preservation of local culture in elementary schools